Human Induced Pluripotent Stem Cell Models of Frontotemporal Dementia With Tau Pathology - Kühn, Rebekka; Mahajan, Aayushi; Canoll, Peter; Hargus, Gunnar (Frontiers in Cell and Developmental Biology, 2021)
Neurodegenerative dementias are the most common group of neurodegenerative diseases affecting more than 40 million people worldwide. One of these diseases is frontotemporal dementia (FTD), an early-onset dementia and one of the leading causes of dementia in people under the age of 60. FTD is associated with atrophy of the frontal and temporal lobes and of additional brain areas causing changes in social behavior, language and cognition. FTD is a heterogeneous group of neurodegenerative disorders with pathological accumulation of particular proteins in neurons and glial cells including the microtubule-associated protein tau, which is deposited in its hyperphosphorylated form in about half of all patients with FTD. As for other patients with dementia, there is currently no cure for patients with FTD and thus several lines of research, including those on patient-derived pluripotent stem cells, focus on the characterization of underlying pathogenic mechanisms with the goal to identify therapeutic targets. In this review, we provide an overview of recent studies reporting disease phenotypes in induced pluripotent stem cell (iPSC)-derived neurons and glial cells from patients with tau-associated FTD with a particular focus on genetic forms of the disease. In addition, we discuss challenges and limitations but also opportunities using differentiated patient-derived iPSCs for disease modeling and biomedical research on neurodegenerative diseases including FTD.